Manufacturing of Indonesian Wooden Traditional Ships - Nofrizal, Nofrizal (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
Traditional ship-building is still widely practiced in Indonesia. Every province and regions have different characteristics in the design and production process of the traditional ships. The production process and procedure of traditional ship is far from the influence of advance technology. This study presents traditional shipbuilding process in the Kepulauan Riau, Indonesia. Survey three traditional shipbuilders in Bintan island, Mana Island, and Kelong island are carried out to get the production process by interviewing master and taking photo for documentation as case study. It is found that strip plank method with both fire and pressing techniques is used in production traditional ship in Kepulauan Riau, Indonesia. L-Joint technique is applied between keel-stem frame and T-joint technique between keel-stern-post.